2005
DOI: 10.1007/s00330-005-2831-9
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved echo-shared parallel MRA of the lung: observer preference study of image quality in comparison with non-echo-shared sequences

Abstract: The aim of this study was to evaluate the image quality of time-resolved echo-shared parallel MRA of the lung. The pulmonary vasculature of nine patients (seven females, two males; median age: 44 years) with pulmonary disease was examined using a time-resolved MRA sequence combining echo sharing with parallel imaging (time-resolved echo-shared angiography technique, or TREAT). The sharpness of the vessel borders, conspicuousness of peripheral lung vessels, artifact level, and overall image quality of TREAT was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…The use of smaller targeted acquisition volumes to cover an area of interest to answer a clinical question focusing on a single arterial segment, might help to overcome limitations in spatial or temporal resolution. Further image acceleration may be achieved by the application of parallel imaging or view sharing techniques (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of smaller targeted acquisition volumes to cover an area of interest to answer a clinical question focusing on a single arterial segment, might help to overcome limitations in spatial or temporal resolution. Further image acceleration may be achieved by the application of parallel imaging or view sharing techniques (8).…”
Section: Discussionmentioning
confidence: 99%
“…More recent developments in MRA include the application of view sharing techniques such as timeresolved imaging of contrast kinetics (TRICKS) and time-resolved echo-shared angiography technique (TREAT) (7,8) as well as image acceleration techniques such as generalized autocalibrating partially parallel acquisitions (GRAPPA) (9) or sensitivity encoding (SENSE) (10), which enable for fast CE-MRA acquisitions and time-resolved MRA (tr-CE-MRA) (7). Although CE-MRA and CTA are less invasive, both methods exclusively depict vessel morphology and geometry but do not provide information about the effect of vascular pathologies on local blood flow characteristics.…”
mentioning
confidence: 99%
“…Its unsurpassed soft-tissue contrast for example has been used for ventilation-perfusion imaging [1][2][3][4][5][6][7][8][9]. MRI of the lung may also be used to detect and measure broadening of tumors invading the chest wall or mediastinal structures [10].…”
Section: Introductionmentioning
confidence: 99%
“…(147)(148)(149) In addition to the above described imaging techniques, MRI offers the possibility to assess perfusion of the lung vascular bed by ultra-fast imaging during the injection of Gadolinium contrast. (150,151) This enables direct visualization of regional perfusion, with the possibility of some form of quantification (though this is notoriously difficult in MRI due to signal-noise properties). Several studies have now demonstrated the feasibility of this technique for assessment of normal and pathological processes.…”
Section: Gadolinium-enhanced Imagingmentioning
confidence: 99%